THEORETICAL STUDY OF THE QUALITY INDICATORS OF NEWLY STRUCTURED KNITTED FABRICS BASED ON A MATHEMATICAL MODEL - Rahmatova, Sadoqat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Mathematical modeling of the physical-mechanical properties and technological indicators of knitted fabrics, along with their theoretical study through practical experiments, creates opportunities to improve the quality indicators of the resulting knitted products and to make preliminary forecasts during the production process. In turn, this leads to an increase in the parameters of achieving economic efficiency through scientific research.